Method for manufacturing a nanodevice based on single-crystalline copper (Cu) thin film and nanodevice having ballistic transport characteristics
A single-crystal copper thin film nano device with removed grain boundaries achieves ballistic transport, addressing electron scattering issues and enabling high-precision patterning for quantum and high-speed electronic applications.
Patent Information
- Application Number
- KR1020250088515
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2025-03-24
- Filing Date
- 2025-07-02
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2045-07-02
AI Technical Summary
Existing technologies face challenges in achieving ballistic transport in copper thin films due to the presence of grain boundaries, which cause electron scattering, limiting the experimental utilization of copper's inherent quantum properties.
A nano device is fabricated using a single-crystal copper thin film grown through atomic sputtering epitaxy, with grain boundaries removed, and a nanometer-width conductive path formed through electron beam lithography and argon ion etching, enabling electron transport without scattering.
The device exhibits negative bend resistance and ballistic conductivity characteristics, preserving electron phase and quantum properties, suitable for high-precision patterning and applications in quantum devices and high-speed electronic devices.
Smart Images

Figure 112025074563893-PAT00007_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to nanoelectronic device technology, and more specifically, to a nano device manufactured based on a single-crystal copper (Cu) thin film and a method for manufacturing the same, wherein the device includes a structure capable of suppressing electron scattering and realizing ballistic conductivity characteristics. Background Technology
[0002] When the free mean path of electrons is longer than the size of the device, the electrons exhibit ballistic transport without being significantly affected by scattering from phonons, rough surfaces, impurities, or crystal defects (e.g., grain boundaries, GBs). Here, a grain boundary is the boundary between two adjacent grains having different crystal orientations. Since quantum information such as electron crystal momentum, spin, and quantum phase is well preserved during ballistic transport, it serves as a means to reveal the intrinsic quantum properties of solid materials.
[0003] Over the past few decades, active research has been conducted on the quantum properties of common metals, including electronic band structures, Fermi plane phases, electrical conductivity, and magnetoresistance. Among these metals, copper (Cu) has a long history of use in electronic circuits due to its excellent conductivity, reliability, and versatility, and is widely utilized in applications ranging from high-speed data cables to interconnects for advanced semiconductor devices. The electronic band structure, Fermi plane phase, and Fermi velocity of bulk Cu are well understood through the de Haas-van Alphen effect, galvanomagnetic phenomena, photoelectron emission, cyclotron resonance, anomalous skin effects, and magnetoacoustics.
[0004] However, growing atomically uniform and flat Cu thin films without crystal defects such as grain boundaries is technically very challenging, and ballistic transport in Cu thin film-based nanostructures has not yet been achieved. This poses a significant limitation to experimentally utilizing the inherent quantum properties of copper.
[0005] In this invention, ballistic transport is experimentally observed in a nano device fabricated based on an atomicly flat single-crystal Cu (111) thin film (SCCF) (Supplementary Fig. 1). The thin film was grown using atomic sputtering epitaxy (ASE) technology, which can overcome the limitations of conventional metal thin film deposition, and can solve problems such as surface oxidation, degradation of electrical performance, and electromigration caused by crystal defects (GB, impurities, etc.).
[0006] The present invention observed negative bend resistance in a device with a cross-shaped structure, which is interpreted as a characteristic of ballistic transport. In an SCCF with a thickness of approximately 90 nm, the free mean path of electrons was estimated to be approximately 150 nm below 85 K (Supplementary Fig. 2). Such an SCCF can be utilized for studying the quantum properties of Cu thin films, including the quantum Hall effect, quantum confinement effect, topological properties, hydrodynamic electron transport, and phase-coherent quantum interference, and this can be extended to research on other metal thin films. Furthermore, it suggests the possibility of practical applications such as quantum circuits, spintronic devices, and copper interconnect technology. Prior art literature
[0007] Korean Published Patent No. 10-20100025870 The problem to be solved
[0008] The objective of the present invention is to provide a nano device capable of realizing ballistic transport characteristics in a low-temperature environment by utilizing a high-quality single-crystal copper (Cu) thin film with removed grain boundaries to minimize electron scattering and implement a structure capable of preserving the phase of electrons, and a method for manufacturing the same.
[0009] In addition, another objective of the present invention is to establish a technical foundation advantageous for future quantum device and high-speed electronic device applications by providing a structure capable of high-precision patterning through electron beam lithography and argon ion milling processes.
[0010] The technical problems that the invention aims to solve are not limited to those mentioned above, and other unmentioned technical problems will be clearly understood by those skilled in the art to which the invention belongs from the description below. means of solving the problem
[0011] A nanodevice having ballistic conductivity characteristics according to the present invention,
[0012] A single-crystal metal thin film having grain boundaries removed, comprising:
[0013] The above single-crystal metal thin film is formed to suppress electron scattering, and
[0014] A conductive path having a nanometer width formed through electron beam lithography and ion etching processes is included, and
[0015] The above conduction path is characterized by exhibiting a nonlinear electrical response in which negative bending resistance occurs during electron transport at low temperatures.
[0016] In addition, the method for manufacturing a nano device based on a single-crystal copper (Cu) thin film according to the present invention is,
[0017] A step of forming a single-crystal copper thin film on a sapphire (Al₂O₃) substrate using an atomic sputtering epitaxy (ASE) method, wherein grain boundaries are removed and the thin film is aligned in the direction of the (111) crystal planes;
[0018] A step of forming a nanometer-width pattern by performing electron beam lithography on the above single-crystal copper thin film;
[0019] A step of forming a conduction path by performing argon (Ar) ion etching based on the above pattern;
[0020] A step of completing a nano device by forming electrodes at both ends of the above-mentioned conduction path; and
[0021] It is characterized by including a step of verifying whether a nonlinear electrical response in which negative bending resistance occurs during electron transport through the above conduction path is exhibited. Effects of the invention
[0022] According to the present invention, by growing a single-crystal copper (Cu(111)) thin film with removed grain boundaries using an atomic sputtering epitaxy (ASE) method, a structure in which electron scattering is suppressed and the phase of electrons is preserved can be realized.
[0023] In addition, by precisely fabricating the device structure to a channel width of 150 nm or less, negative bend resistance characteristics can be confirmed in a low-temperature (e.g., 1.7 K) environment, thereby experimentally demonstrating ballistic conductivity characteristics with almost no scattering in the electron transport path.
[0024] Therefore, the present invention dramatically improves conductivity efficiency compared to existing polycrystalline metal thin film-based devices and provides a technical foundation applicable to advanced application fields such as quantum devices, high-speed switching devices, and low-power nanodevices. Brief explanation of the drawing
[0025] FIG. 1 is a ballistic transport image in a single-crystal Cu (111) thin film according to an embodiment of the present invention, (a) a scanning electron microscope (SEM) image of a Hall bar device with a channel width W=150 nm and an inset is an enlarged image of the indicated area. (b) a cross-sectional TEM image obtained by cutting with a focused ion beam (FIB). (c) a diagram of bending resistance (RB) measurements, in which the electron trajectories of diffusive transport and ballistic transport are indicated by blue and red arrows, respectively. (d) a diagram showing the temperature dependence of RB for devices with W=10 μm, 1 μm, 250 nm, and 150 nm, where the circular symbols are the fitting results of the Bloch-Gruneisen function. Figure 2 shows grain boundaries (GB) and twin boundaries (TB) in PCCF and SCCF according to an embodiment of the present invention, (a) a map of the difference in crystal orientation and an enlarged image of PCCF, where GB and TB are indicated by blue and red lines, respectively. (b) an electron backscatter diffraction (EBSD) map of PCCF showing random alignment. (c) an SEM image of PCCF showing a rough surface and GB. (d~i) microstructure analysis images of SCCF with reduced GB and SCCF with completely removed GB. Figure 3 is an electrical transport image according to the GB length according to an embodiment of the present invention, (a) the relationship between the termination resistance measured at 4.3 K in a W=1 μm device and the GB length L_GB. (b) the relationship between the normalized bending resistance RB and L_GB in a W=150 nm device. FIG. 4 shows bending resistance and geometric effects according to a magnetic field according to an embodiment of the present invention, wherein (a) symmetrical bending resistance (R) in a magnetic field B s ) This is a measurement schematic. (b) Bending resistance (R) at W=1 μm, 250 nm, and 150 nm devices B s This is an image showing the dependence of ) on the magnetic field (B). (c) Hall resistance (ρ xy) Measurement diagram. (d~e) Asymmetric Hall resistances measured at 120 K (d) and 1.7 K (e) in SCCF devices with varying W. (fg) Fermi planes calculated from Cu (111) of 2D and 1D structures. Specific details for implementing the invention
[0026] The terms used in this specification will be briefly explained, and the invention will be described in detail.
[0027] The terms used in this invention have been selected based on currently widely used general terms while considering their functions within the invention; however, these terms may vary depending on the intent of those skilled in the art, case law, the emergence of new technologies, etc. Therefore, the terms used in this invention should be defined not merely by their names, but based on their meanings and the overall context of the invention.
[0028] When a part of a specification is described as “comprising” a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.
[0029] Embodiments of the present invention are described below with reference to the attached drawings so that those skilled in the art can easily implement them. However, the present invention may be embodied in various different forms and is not limited to the embodiments described herein.
[0030] Specific details regarding the problem to be solved by the present invention, the means for solving the problem, and the effects of the invention are included in the embodiments and drawings described below. The advantages and features of the present invention, and the methods for achieving them, will become clear by referring to the embodiments described below in detail together with the accompanying drawings.
[0031] Hereinafter, the present invention will be described in more detail with reference to the attached drawings.
[0033] The present invention relates to a nanoelectronic device utilizing the phenomenon of electron ballistic transport, and to understand this, the basic concepts and conditions of electron transport are described.
[0034] Ballistic transport refers to a mode of electron movement in which electrons travel within a solid along a nearly straight path without scattering from grain boundaries, impurities, or lattice vibrations (phonons). In such ballistic transport, the electron's momentum, phase information, and quantum state are conserved (coherent) with minimal external interference, which is fundamentally distinct from general diffusive transport.
[0035] Electron-phonon interactions may still exist, but this does not necessarily imply inelastic scattering leading to energy or momentum loss. In particular, in low-temperature environments where the number of phonons decreases, the probability of scattering due to these interactions is significantly reduced, allowing electrons to travel long distances while maintaining a quantum coherent state. This leads to phenomena such as quantum interference and coherent oscillation, which serve as a core physical basis for the design of high-speed electronic devices and quantum computing devices.
[0036] For ballistic transport to occur, the following conditions must be met.
[0037] First, a low-temperature environment is required. As the temperature decreases, the number of phonons within the crystal decreases, which significantly reduces the possibility of electron scattering. In the embodiments of the present invention, these ballistic conduction characteristics were stably observed in an environment of about 85K or lower.
[0038] Second, a highly crystalline single-crystal structure is required. In particular, in this invention, a single-crystal copper (Cu) thin film aligned in the (111) plane direction was formed using an atomic sputtering epitaxy (ASE) process, and the grain boundaries were substantially eliminated in this thin film to maximize the mean free path of electrons.
[0039] Third, it is necessary to implement a nanostructured conduction path. The narrower and clearer the boundary of the electron's path, the higher the probability that incident electrons will reach the exit without scattering, which promotes the implementation of ballistic conduction. In the present invention, a nanostructured conduction path having a channel width of about 150 nm or less was implemented through lithography and ion etching processes.
[0040] When an environment is established in this way where electrons can move without energy loss or scattering, the device exhibits a nonlinear electrical response, such as negative bend resistance. This phenomenon occurs due to the direct transfer of electrons between electrodes and is used as a key measurement indicator of the present invention.
[0041] In summary, the present invention provides potential applications in various high-performance semiconductor systems, such as low-loss signal transmission circuits based on electron interference, quantum devices, and high-speed nanoelectronic devices, by realizing a ballistic transport mechanism in which the quantum state and phase of electrons are preserved. In particular, the single-crystal copper thin film-based nanoconductive structure implemented in this invention effectively suppresses electron scattering and heat generation problems that occur in conventional polycrystalline metal structures, and provides a technical foundation highly suitable for intermetallic interconnects in semiconductor packages and low-temperature operating quantum circuits.
[0042] The single-crystal copper thin film-based nanodevice of the present invention can be applied to metal-interconnect structures inside semiconductor chips where the loss of high-speed electronic signals must be minimized.
[0043] In particular, the single-crystal copper (Cu(111)) thin film, in which the grain boundaries are removed to suppress electron scattering, and the nanometer-wide conduction path secure an average free path capable of ballistic transport, thereby minimizing resistance loss and heat generation.
[0044] In addition, since the nanodevice of the present invention possesses stable electron interference characteristics in a low-temperature environment, it can also be applied as a conduction channel within a quantum interference-based quantum device or a spintronic device.
[0045] For example, the structure of the present invention, in which negative bending resistance is observed in an environment of 85K or lower, can be used as an electron transport path that maintains phase information in a quantum device circuit requiring low-temperature operation.
[0047] 1. Nanodevice with ballistic conductivity properties
[0048] The present invention relates to a nanoelectronic device capable of realizing ballistic transport characteristics and a method for manufacturing the same, based on a single-crystal metal thin film in which grain boundaries are removed, particularly a single-crystal copper (Cu) thin film aligned along the (111) crystal plane. The core of the present invention is to create an environment in which electrons can move without scattering by forming a conduction path within the single-crystal metal thin film having a channel narrower than the mean free path of electrons, thereby enabling the expression of negative bend resistance, which is one of the nonlinear electrical responses.
[0049] The metal thin film used in the present invention is grown through an atomic sputtering epitaxy (ASE) process and is formed on a sapphire (Al₂O₃) substrate with a thickness of 10 to 90 nm. The ASE process is performed at the single-atom level so that grain boundaries are not formed, and copper atoms are oriented toward the (111) crystal plane. The single-crystal copper thin film grown in this way contains only twin boundaries, and high crystallinity can be secured by removing grain boundaries, which are the main cause of electron scattering.
[0050] The thickness of the single-crystal copper thin film formed in the present invention can be controlled to a range of 20 to 90 nm, and in this range, sufficient ballistic conductivity characteristics can be achieved without phase loss of electrons.
[0051] Double-sided polished sapphire (Al₂O₃) is used as the substrate, and the vacuum level is 2×10⁻⁶ -7 Torr, working pressure 5.4×10⁻⁶ -3 The deposition process was performed under conditions of Torr, RF power of 30W, and substrate temperature of approximately 170℃.
[0052] On the above single-crystal copper thin film, a nanometer-width pattern (e.g., 50–150 nm width) is formed using electron beam lithography, and then a conduction path is defined through an argon ion milling process. The conduction path is formed by etching only a portion of the film thickness without completely penetrating the thin film, and forms a channel structure through which electrons can flow directly without scattering. Such a nanostructured conduction path becomes a key structural element that induces quantum ballistic transport phenomena instead of classical diffusion conduction.
[0053] When forming a conduction path, argon ion etching does not completely penetrate the thin film, but forms a path by removing only about 30 to 50 percent of the thin film thickness, thereby preventing an electrical short circuit between the lower electrode and the insulating layer.
[0054] Since the nanodevice of the present invention has a structure that minimizes electron scattering and power loss, it can be applied to inter-metal interconnects within semiconductor chips, low-loss signal transmission circuits, and even quantum devices operating at low temperatures. In particular, the structure of the present invention can effectively suppress problems such as electron scattering, electromigration, and Joule heating that occur in conventional polycrystalline metal wiring, which serves as an important technical foundation for the design of next-generation high-density integrated circuits and the realization of quantum information devices.
[0055] Thin film formation via the ASE method is at a basic vacuum of 2×10 -7 Torr, working pressure 5.0×10 -3 Up to 6.0X10 -3 Torr (approx. 5.4×10⁻⁶ -3It is performed under conditions of Torr, a substrate temperature of 165 to 175 °C (approx. 170 °C), and an RF power of 30 W, and is optimized for maintaining high crystallinity. Subsequently, e-beam lithography and ion etching processes are key steps required to reproducibly realize conductive paths with a line width of 250 nm or less, and process variables such as lithography pattern formation, alignment error, and etching depth are directly related to the electrical characteristics of the device.
[0056] The ASE process is 2×10 -7 It is performed in an ultra-high vacuum environment of Torr, and this vacuum range is essential to prevent impurity adsorption and ensure high crystallinity.
[0057] The width of the nanoconducting path defined by electron beam lithography is in the range of about 250 nm or less, which is set to be shorter than the electron mean free path and satisfies ballistic transport conditions.
[0059] 2. Method for manufacturing nanodevices based on single-crystal copper thin films
[0060] The present invention relates to a method for manufacturing a nanodevice that minimizes electron scattering and exhibits a nonlinear electrical response based on a highly crystalline single-crystal copper (Cu) thin film. Specifically, the method comprises a series of processes including growing a single-crystal copper thin film with grain boundaries removed using an atomic sputtering epitaxy (ASE) method on a sapphire substrate, forming a nanoconducting path through electron beam lithography and argon ion etching processes, completing the device by depositing electrodes at both ends, and verifying the performance of the device by evaluating the nonlinear response in a low-temperature environment.
[0061] A double-sided polished sapphire (Al₂O₃) substrate aligned in the (0001) direction is used as the substrate. A single-crystal copper thin film is grown on this substrate by performing an ASE process.
[0062] The ASE process has a vacuum level of 2×10 -7Torr, working pressure approx. 5.4×10⁻⁶ -3 The process is carried out under conditions of Torr, substrate temperature of approximately 170°C, and RF power of approximately 30W, and copper atoms deposited using high-energy ions are epitaxially aligned on the surface of the substrate.
[0063] The copper thin film formed in this process has a high-quality single-crystal structure in which grain boundaries are not formed, the (111) planes are aligned, and only twin boundaries exist. The thickness of the thin film is usually formed in the range of 10 to 90 nm, which affects the etching depth and electron transport distance in subsequent processes.
[0064] After a single-crystal copper thin film is formed, a nanoconductive path pattern with a width of 250 nm or less is defined through electron beam lithography. The pattern is formed using a PMMA photoresist, and the resolution can be adjusted to the level of tens of nanometers.
[0065] Subsequently, argon (Ar) ion etching is performed based on a defined pattern. At this time, the ion beam is controlled so that it does not completely penetrate the thin film but removes only about 30 to 70% of its thickness. As a result, the conductive path formed inside the copper thin film is not short-circuited with the underlying structure and serves as a channel that enables horizontal ballistic transport of electrons.
[0066] Gold (Au) electrodes are formed at both ends of the formed conduction path using vacuum deposition. The electrodes are designed to minimize contact resistance with the device, and a patterning process is performed in parallel to ensure precise alignment with the conduction path.
[0067] The completed structure includes nanoconductive channels within a single-crystal copper thin film, and the entire device can also be implemented as a multi-channel structure including 1 to 10 channels.
[0068] The fabricated device is subjected to current-voltage (IV) characteristic measurements in a low-temperature environment of 85K or lower, and negative bend resistance is observed. This is a typical quantum transport phenomenon that occurs when electrons flow without scattering along a conduction path shorter than their mean free path.
[0069] This device can be applied as a component of metal-to-metal interconnects or low-temperature operating quantum devices within semiconductor chips. In particular, thanks to structural characteristics that suppress electron scattering, it can provide lower loss, lower heat generation, and higher reliability compared to conventional metal wiring.
[0071] Hereinafter, the present invention will be explained in more detail through comparative examples and embodiments prepared by conventional methods and experimental examples. The purpose, features, and advantages of the present invention will be easily understood through the following embodiments. The present invention is not limited to the embodiments described herein and may be embodied in other forms. The embodiments introduced herein are provided to ensure that the concept of the present invention is sufficiently conveyed to those skilled in the art to which the present invention pertains. Therefore, the present invention should not be limited by the following embodiments.
[0073] Example 1: Formation of a single-crystal copper (Cu) thin film
[0074] A sapphire (Al₂O₃) (0001) substrate was cleaned in an ultrasonic cleaner with acetone, IPA, and DIW for 10 minutes each, and then heat-dried at 120°C for 10 minutes. Subsequently, the prepared substrate was mounted in the chamber of an ASE (atomic sputtering epitaxy) device, and a base vacuum of approximately 2×10⁻⁶ -7 Torr, working pressure approx. 5.4×10⁻⁶ -3 Sputtering using a copper target was performed under conditions of Torr, substrate temperature of 170℃, and RF power of 30W.
[0075] The deposition time was set to about 30 minutes, and a single-crystal copper thin film with a thickness of about 70 nm was grown. The crystal structure of the thin film was confirmed to be a single-crystal structure aligned in the (111) plane direction through X-ray diffraction (XRD) and electron backscatter diffraction (EBSD) analysis, and no grain boundaries were observed except for twin boundaries.
[0077] Example 2: Patterning of nanoconductive pathways
[0078] A PMMA (950k, A4) photoresist was spin-coated onto the formed single-crystal copper thin film to a thickness of about 100 nm, and then soft-baked at 180°C for 90 seconds.
[0079] A nanoconducting path pattern with a width of approximately 100 nm and a length of approximately 2 μm was defined using an electron beam lithography device (Vistec EBPG 5200). After exposure, the photoresist was developed in an MIBK:IPA (1:3) developer for 60 seconds.
[0081] Example 3: Channel formation via argon ion etching
[0082] Argon (Ar) ion beam etching was performed using the developed pattern as a mask. The ion acceleration voltage was set to 300 eV and the etching time to approximately 80 seconds, so that only about 60% of the total thickness was etched, leaving the bottom of the copper thin film intact. As a result, a non-penetrating nanochannel structure was formed.
[0084] Example 4: Electrode Formation and Device Completion
[0085] Cr / Au (5 nm / 50 nm) metal electrodes were deposited at both ends of the conduction path using vacuum thermal deposition, and then patterned through a lift-off process. The distance between the electrodes was set to approximately 2 μm.
[0087] Experimental Example 1: Ballistic transport in a single-crystal Cu (111) thin film (SCCF)
[0088] Using standard electron beam lithography and argon ion etching processes, Hall bar-shaped devices with various channel widths (W) of 10 μm, 1 μm, 250 nm, and 150 nm were fabricated, with a thickness (t) of approximately 90 nm (Fig. 1a, b). A cross-sectional TEM image of the device shows a perfectly aligned arrangement of copper atoms along the
[0111] direction of the thin film at intervals of 2.07 Å (Fig. 1b), indicating that the high crystal quality of the thin film was maintained even after the patterning process.
[0089] Bending resistance (R B = V B / I) was measured in a cross-type structure (Fig. 1c), where the current (I) is applied from terminals 1 to 5, and the bending voltage (V B ) was measured between terminals 3 and 4. The mean free path of electrons (l mfp In the diffusion transport region where ) is shorter than the device size, the bending resistance R B is the van der Pauw equation in a symmetric intersection structure ( R B =( ρ ln2) / ( t It can be expressed as π). In this diffusion transport region, due to the material's intrinsic resistivity (ρ), R B is expected to be positive. The temperature dependence of ρ in diffusing metals is dominated primarily by electron-acoustic phonon scattering, which follows the Bloch-Gruneisen equation (Equation 1) derived from Boltzmann transport theory:
[0091] [Equation 1]
[0092]
[0094] Here, ρ0 is the residual resistance due to temperature-independent defects such as GB and impurities, and α el-ph Θ is the electron-phonon coupling strength. R represents the Debye temperature.
[0095] As shown in Fig. 1d, R in the device with W = 10 μm and 1 μm B The temperature dependence of is in good agreement with Equation 1, and the fitted parameter thereis α el-ph = 8.8×10 -8 , Θ R = 270 K. This suggests that diffusion transport is dominant across the entire temperature range. In fact, R obtained through the van der Pauw equation B From the resistivity (ρ) calculated using, the mean free path (l) through the following equation mfp Can calculate )
[0097] [Equation 2]
[0098]
[0100] For a W = 10 μm device, l at T = 1.7 K mfp = Calculated as 170 nm, which is shorter than the width of the device.
[0101] However, for devices with W ≤ 250 nm, R predicted by the Bloch-Gruneisen equation B A clear difference was observed between (T) and the actual measured value. In particular, for the device with W = 150 nm, R at 90K or below B It showed a negative value. While such counterintuitive negative bending resistance has been observed in high-mobility 2D electronic systems such as GaAs / AlGaAs heterojunctions or graphene, it has never been observed in metal thin films.
[0102] In the ballistic transport region, electrons injected at terminal 5 can move directly to terminal 3 without scattering (refer to the red arrow in Fig. 1c), and as electrons accumulate around terminal 3, a negative potential is formed, R B It decreases and eventually takes on a negative value.
[0103] Through these results, it was confirmed that the ballistic transport characteristics within the SCCF, which were previously hidden due to electron scattering by the GB, were revealed when the GB was completely removed.
[0105] Experimental Example 2: Structural Defects in Single SCCF and Polycrystalline Cu Thin Films (PCCF)
[0106] We analyzed the crystallographic microstructure of a single-crystal Cu (111) thin film (SCCF) to confirm the high crystallinity essential for ballistic transport. During the thin film growth process, grain boundaries (GBs) and twin boundaries (TBs) are formed due to lattice mismatch with the substrate. While the formation of TBs is unavoidable, the formation of GBs can be minimized by using a growth technique that accounts for extended interatomic distance mismatch (EADM).
[0107] We investigated the distributions of GB and TB for PCCF (Figs. 2a, b, c), SCCF including some GB (Figs. 2d, e, f), and SCCF without GB (Figs. 2g, h, i) using the following three analysis methods:
[0108] - Misorientation line mapping
[0109] - Electron Backscatter Diffraction (EBSD),
[0110] - Scanning Electron Microscope (SEM) analysis.
[0112] In Fig. 2, GB and TB are represented by blue and red lines, respectively. PCCF generally has many grains, and both GB and TB exist. A typical 2-inch PCCF wafer contains trillions (10 12 There are crystal grains (Fig. 2a), and each crystal has a different orientation.
[0113] Cu thin films grown by the ASE method are almost perfectly aligned with respect to the (111) plane (Fig. 2e) and may contain some GBs (Fig. 2d). However, the GBs observed in the misorientation line map of Fig. 2d are only about 1-2° off from the ideal TB condition (60° rotation) and are not detected as different grains in EBSD. Nevertheless, since these GBs can affect electron transport, only SCCFs without any GBs were used in this study.
[0114] Normally grown SCCF (Fig. 2g) has no GB and contains only TB. As shown in Fig. 2i, the crystal orientation is divided into only two types, I and II, which follow an ABC…, ACB… stacking structure and have a 60˚ rotational symmetry relationship with respect to the (111) axis.
[0115] While TB density may vary slightly depending on location, the overall density remains constant. TB has almost no effect on electrical resistance for the following reasons:
[0116] - No charge defects are formed around TB, so there is almost no change in potential.
[0117] - Since the crystal grains on both sides of TB align well with the Fermi plane of Cu upon 60˚ rotation, scattering of incident electromagnetic waves is suppressed.
[0118] In conclusion, it was theoretically and experimentally confirmed that the SCCF used in this study has GB completely removed and that the presence of TB does not significantly affect electron transport characteristics.
[0120] Experimental Example 3: Electric transport characteristics according to grain boundaries (GB)
[0121] Figure 3 shows the electrical transport behavior according to the GB length (LGB), which is the total length of the line segments separating the grains, in a mis-orientation line map of an area of 7.7 μm × 22.7 μm measured by the EBSD technique. Generally, since GBs act as electron scattering points, the resistivity increases as the number of GBs increases. Therefore, as the grain size (d) decreases, that is, as the LGB increases, the contribution of resistance due to GBs increases. Mayadas and Shatzkes (MS) studied a more quantitative model explaining electron scattering at GBs. According to the MS model, as shown in Equation 3, the resistivity decreases as the grain size (d) increases, and the resistivity increases as the electron scattering probability (S) at GBs increases. According to the present invention, by implementing a structure that suppresses electron scattering and preserves the phase of electrons based on a single-crystal copper (Cu(111)) thin film with removed grain boundaries, ballistic conductivity characteristics can be realized in a low-temperature environment. In particular, it is experimentally confirmed that negative bending resistance appears through a precise nanodevice structure with a channel width of 150 nm or less, which implies securing a movement path without electron scattering. Furthermore, a manufacturing process combining the ASE growth method with electron beam lithography and ion etching enables the stable formation of high-quality single-crystal thin films and the fabrication of highly reproducible nanodevices, providing a technological foundation that can be utilized in various future applications such as quantum devices and high-speed switching devices.
[0123] [Equation 3a]
[0124]
[0126] [Equation 3b]
[0127]
[0129] Here, ρ g represents the resistivity due to electron scattering at the GB, and ρ irepresents the resistivity due to other causes such as acoustic phonons, impurities, and GBs. As shown in Fig. 3a, the resistivity of the device with W=1 μm at 4.3 K is in the diffusion transport region, and in a two-dimensional system, d∝(LGB) -1 It satisfies the relationship and is in good agreement with MS theory. Figure 3b shows the LGB dependence of RB at 4.3 K, normalized based on the value at 285 K, for the W=150 nm device. Since the W=1 μm device is in a diffusion transport state at all LGB values, the normalized RB also exhibits an LGB dependence similar to that of resistivity. However, for the W=250 nm and 150 nm devices, L GB It gets smaller l mfp If becomes longer than W, R B g has a negative value, and the MS model cannot explain this.
[0131] Experimental Example 4: Geometric effects in SCCF transport measurements
[0132] To study the ballistic transport behavior under a magnetic field in more detail, we bend resistance
[0133] R B The magnetic field dependence of was investigated (Fig. 4). To reduce signal mixing caused by minute asymmetry and alignment misalignment between contacts R B was symmetrical. Magnetic field B It was applied perpendicularly to SCCF parallel to the (111) direction. As the magnitude of |B| increases, electrons are deflected by the Lorentz force, and the number of electrons reaching the opposite terminal 3 decreases, resulting in symmetrical bending resistance. R B S gradually increases (Fig. 4a). This ballistic transport phenomenon can be qualitatively explained using the Landauer-Buttiker approach.
[0134] R B S is the forward transmission probabilityP FW , probability of left turn delivery P L , right turn delivery probability P R It can be expressed as and is equal to Equation (4):
[0136] [Equation 4a]
[0137]
[0138] [Equation 4b]
[0139]
[0141] In the absence of a magnetic field (B=0) P FW go P L class P R Because it is much larger than ( P L P R - P FW 2 becomes negative, so R B S It becomes <0. When a magnetic field is applied, the trajectory of the electron bends due to the Lorentz force, and P FW is decreasing and P L or P R As it increases, R B S becomes larger. As can be seen in Fig. 4b, R depending on the magnetic field B S The magnitude of the increase is more pronounced in the ballistic transport region (W = 150 nm) compared to the diffusion transport region (W = 1 μm). This is because electron trajectories are more clearly defined in the ballistic region.
[0142] Antisymmetric Hall Resistance ρ xy asIt increases linearly with the magnetic field like a typical metal thin film at 120 K (Fig. 4d), but becomes nonlinear at 1.7 K (Fig. 4e), and the slope decreases as the device width increases. The difference with temperature may be due to changes in the Fermi surface phase caused by chemical potential shifts with temperature change. Recent studies have suggested that this nonlinear Hall effect in SCCF (111) is due to hole carrier-dominant transport, which was confirmed through two-carrier model fitting analysis.
[0143] The nonlinear Hall effect observed at 1.7 K in samples with W = 10 μm and 1 μm is consistent with previous research findings that electrons and holes coexist in SCCF without GBs in thin films with a thickness of 205 nm or less. In devices of this width, although the film is 90 nm thick, electrons can behave without isolation thanks to the micrometer-scale pattern size. However, when the width is reduced to 250 nm or less, the Hall effect becomes linear again (Fig. 4e), indicating that the carriers have shifted to an electron-centered state.
[0144] To explain the linear return phenomenon of this Hall effect, we calculated and compared the effective band structures of a 2D Cu (111) thin film (Fig. 4f) and a 1D Cu (111) rod (Fig. 4g) for a specific k-point. In the band structure of the 2D thin film, electron and hole orbits are clearly separated, but the band structure of the 1D structure becomes much more complex due to quantum confinement effects in both the vertical and planar directions.
[0145] The Fermi surface of the 2D thin film exhibits quantum-confined bands along the
[0111] direction (Fig. 4f, left panel), while the Hall band is dominant in the Fermi surface represented by the periodic zone scheme (Fig. 4f, right panel). In contrast, the Fermi surface of the 1D structure shows almost no distinct structure and is difficult to provide physical insights into. To overcome this, we calculated the effective Fermi surface by band unfolding the 1D structure into 2D (Fig. 4g, left panel). In the unfolded periodic zone scheme, the Hall band is significantly reduced, and electron orbits become dominant (Fig. 4g, right panel). Although the calculated system size is smaller than that of an actual device, it clearly demonstrates the tendency for the Hall orbits to decrease as the system geometry approaches 1D.
[0146] These calculation results qualitatively explain the phenomenon where the experimentally observed two-carrier model-based nonlinear Hall effect (NHE) transitions into a linear Hall effect as the device width W decreases.
[0148] In this invention, ballistic electron transport was observed in a Cu (111) thin film-based nanodevice, and the transport characteristics were investigated as to how they depend on the quality of the thin film. A Hall bar-shaped device was fabricated using an atomically flat 90 nm thick single-crystal Cu (111) thin film (SCCF), and negative bending resistance, which is direct evidence of ballistic transport, was observed. Under a normal magnetic field, the ballistic electrons were hindered, and the bending resistance increased. In addition, the distribution of grain boundaries (GB) and twin systems (TB) within the sample was analyzed through EBSD measurements, and it was shown that the resistance of the Cu thin film device is mainly determined by GB and is not sensitive to TB. Furthermore, through experimental observation and theoretical analysis, it was confirmed that as the Cu (111) thin film transitions from a two-dimensional to a one-dimensional boundary, the Hall orbits observed in the two dimensions disappear, which suggests that the nonlinear Hall effect caused by dual carriers transitions into a linear Hall effect.
[0149] These findings not only provide a new platform for studying the inherent quantum mechanical properties of Cu but also offer significant implications for the development of high-performance electronic and spintronic devices by preserving quantum information such as momentum, quantum phase, and spin. Furthermore, they can contribute to resolving reliability issues in semiconductor technology, such as Joule heating and electromigration in Cu interconnects. Recent research has revealed that the Fermi surface of Cu possesses topologically non-trivial properties, which is expected to open up new possibilities for phase-related experiments within ballistic metals.
[0150] As such, those skilled in the art to which the present invention pertains will understand that the technical configuration of the present invention described above can be implemented in other specific forms without altering the technical concept or essential features of the present invention.
[0151] Therefore, the embodiments described above should be understood as illustrative in all respects and not limiting, and the scope of the invention is defined by the claims set forth below rather than by the detailed description above, and all modifications or variations derived from the meaning and scope of the claims and equivalent concepts thereof should be interpreted as being included within the scope of the invention.
Claims
Claim 1 A single-crystal metal thin film having grain boundaries removed, wherein the single-crystal metal thin film is grown on a sapphire (Al₂O₃) substrate by an atomic sputtering epitaxy (ASE) method. (111) A single-crystal copper (Cu) thin film aligned in the direction of the crystal plane, containing only twin boundaries and not grain boundaries, having a thickness of 10 nm or more and 90 nm or less, formed on a sapphire substrate aligned in the direction (0001), formed to suppress electron scattering, and includes a conduction path having a nanometer width formed through electron beam lithography and ion etching processes, wherein the ion etching is argon (Ar) ion etching, wherein the conduction path is a Hall bar structure with a width of 50 to 150 nm and a length of 2 μm, and is a non-penetrating structure in which a continuous copper layer remains below the conduction path because it does not completely penetrate the single-crystal copper thin film, and wherein the conduction path is formed by removing only 30 to 70% of the thickness of the single-crystal copper thin film, A nanodevice having ballistic conductivity characteristics, wherein Cr / Au metal electrodes are formed at both ends of the conduction path, the conduction path is formed with 1 to 10 channels, and the conduction path exhibits a nonlinear electrical response in which negative bending resistance occurs during electron transport at low temperatures. Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 A nano-device having ballistic conductivity characteristics, wherein, in claim 1, the nano-device is capable of operating at a low temperature of 85K or lower. Claim 7 A nano-device having ballistic conductivity characteristics, wherein, in claim 1, the nano-device determines whether electrons are ballistic transported by measuring negative bending resistance. Claim 8 A nano-device having ballistic conductivity characteristics, characterized in that, in claim 1, the nano-device is applied to a metal-to-metal interconnect or a low-loss signal transmission circuit of a semiconductor device. Claim 9 delete Claim 10 delete Claim 11 On a double-sided polished sapphire (Al₂O₃) substrate aligned in the (0001) direction, at a vacuum of 2×10 -7 A step of forming a single-crystal copper thin film having a thickness of 10 to 90 nm, with grain boundaries removed and aligned in the direction of (111) crystal planes, and containing only twin boundaries, using an atomic sputtering epitaxy (ASE) method under Torr conditions; a step of performing electron beam lithography on the single-crystal copper thin film to form a nanometer-width pattern having a Hall bar structure of length 2 μm and a line width of 50 to 150 nm; a step of performing argon (Ar) ion etching based on the pattern to form a conduction path by removing only 30 to 70% of the total thin film thickness without completely penetrating the copper thin film; and a step of forming Cr / Au (5 nm / 50 nm) metal electrodes at both ends of the conduction path. A method for manufacturing a nano device based on a single-crystal copper (Cu) thin film, characterized by including the step of completing the nano device; and the step of measuring the device at a temperature of 85 K or lower to confirm a nonlinear electrical response in which negative bending resistance occurs during electron transport. Claim 12 delete Claim 13 delete Claim 14 delete Claim 15 delete Claim 16 delete Claim 17 A method for manufacturing a nano device based on a single-crystal copper (Cu) thin film, characterized in that, in claim 11, the device is applied to metal-to-metal interconnects within a semiconductor chip or to a low-temperature operating quantum device.
Citation Information
Patent Citations
Single crystal copper foil and Anode-free rechargeable lithium metal battery comprising the same
KR1020240142174A
Nanostructures including a metal
US20050064158A1
Method for Dry Etching of Copper Thin Films
KR1020230085507A
Manufacturing method for single crystal copper thin film containing nonlinear hall effect and hole carrier dominant transport phenomenon in two-dimensional single crystal thin film with suppressed grain boundary and single crystal copper thin film and single crystal copper thin film semi-conductor thereof
KR1020240175308A
Metallic nanostructures
US20080206555A1
